Work Professionalism Through Work Discipline on Employee Performance (a Literature Study Human Resource Management) - Asgaruddin Asgaruddin (Dinasti Publisher, 2023)
Previous research or relevant research is very crucial in research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or the influence between variables. This article reviews the effect of work professionalism on employee performance through work discipline, either directly or indirectly. This article is a literature study of human resource management conducted with a literature review or literature research that examines or critically reviews knowledge, ideas, or findings in the body of academic-oriented literature, and also formulates the theoretical and methodological contributions for a particular topic. The results of this library research are: 1) work professionalism affects work discipline; 2) work discipline affects performance; 3) work discipline affects performance, and 4) work professionalism affects performance through work discipline.